Sequential carotenoids extraction and biodiesel production from Rhodosporidium toruloides NCYC 921 biomass - Passarinho, Paula C. (2019)
ABSTRACT: A new process for co-extraction and separation of fatty acids and carotenoids from Rhodosporidium toruloides NCYC 921 biomass in order to achieve full exploitation of the yeast lipidic fraction is described. A saponification of the wet yeast biomass was performed using a potassium hydroxide solution (1.1 M) in ethanol 96%, at 65 °C for 180 min. In the carotenoid extraction step, a biphasic system with an organic: aqueous phases ratio of 0.49 mL/mL and a water content of 18.9% (w/w) was used. In the presence of an acid catalyst, the fatty acid fraction was esterified into fatty acids ethyl esters. The yeast biomass downstream processing allowed reaching a fatty acid and total carotenoids recovery yields of 91.0% and 85.2%, respectively. The process reported here takes advantage of various components of the yeast biomass, therefore maximizing the value derived from the biomass feedstock, with a minimal environmental impact within the frame of circular bioeconomy.